CRISPR/Cas9 Approach to Generate an Auxotrophic BCG Strain for Unmarked Expression of LTAK63 Adjuvant: A Tuberculosis Vaccine Candidate - Moraes, Luana; Trentini, Monalisa Martins; Fousteris, Dimitrios; Eto, Silas Fernandes; Chudzinski-Tavassi, Ana Marisa; Leite, Luciana Cezar de Cerqueira; Kanno, Alex Issamu (Frontiers in Immunology, 2022)
Tuberculosis is one of the deadliest infectious diseases and a huge healthcare burden in many countries. New vaccines, including recombinant BCG-based candidates, are currently under evaluation in clinical trials. Our group previously showed that a recombinant BCG expressing LTAK63 (rBCG-LTAK63), a genetically detoxified subunit A of LT toxin from Escherichia coli, induces improved protection against Mycobacterium tuberculosis (Mtb) in mouse models. This construct uses a traditional antibiotic resistance marker to enable heterologous expression. In order to avoid the use of these markers, not appropriate for human vaccines, we used CRISPR/Cas9 to generate unmarked mutations in the lysA gene, thus obtaining a lysine auxotrophic BCG strain. A mycobacterial vector carrying lysA and ltak63 gene was used to complement the auxotrophic BCG which co-expressed the LTAK63 antigen (rBCGΔ-LTAK63) at comparable levels to the original construct. The intranasal challenge with Mtb confirmed the superior protection induced by rBCGΔ-LTAK63 compared to wild-type BCG. Furthermore, mice immunized with rBCGΔ-LTAK63 showed improved lung function. In this work we showed the practical application of CRISPR/Cas9 in the tuberculosis vaccine development field.